CHARACTERISTICS OF HYDROGEOLOGICAL MASSIVES OF THE GREATER, LITTLE CAUCASUS AND TALYSH (AZERBAIJAN) TAKING INTO ACCOUNT GLOBAL CLIMATE CHANGE - Tagiyev, I.; Kerimov, V.; Sherifov, J. (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2025)
Issues of global warming lead to dramatic changes in hydrological and hydrogeological conditions. The Caspian Sea and mountain ranges have a great influence on the formation of the climate. Many believed that climate models and predictions are probabilistic in nature, but some will think that global climate change is important today. It is necessary to take into account that climate change is global, it occurs everywhere on our planet and affects every state and every person. Purpose: Clarification of the influence of the relief and the proximity of the Caspian Sea which determines the differences and distribution of air temperature, precipitation and other climate elements. The annual amount of precipitation falls in the cold half of the year in the form of snow, the melting of which causes violent spring floods on the rivers, evaporation and sufficient relative moisture. The characteristics of climatic zones show their close relationship with the nature of the relief and with the hypsometric position of the terrain above sea level. Ground waters within the Greater, Lesser Caucasus and Talysh are distributed everywhere. In the Greater Caucasus, there are mainly distributed gravels of the Kusar Formation (QIV), and within the Khvalynskaya, Khazar, Bakinskaya and Kusarskaya formations, clay interlayers divide the general flow of groundwater into several horizons of pressure water, the same pattern also takes place in the Lesser Caucasus and Talysh. Climate change, the nature of precipitation distribution, the growing season of plants, pH-pH, an increase in the average global temperature causing various side effects, the frequency of extreme weather events, a rise or decrease in the water level, ultimately all this affects all elements of the hydrological river systems and calculated industrial reserves of groundwater. Deforestation contributes to global warming and one of the main reasons for the intensification of the greenhouse effect, negatively affects the water cycle, the transpiration process stops. We should participate in the process of reducing CO2 emissions, pay attention to the increase of forest areas, reduction of water pollution, transfer to unconventional renewable solar and wind power, accelerate the introduction of alternative energy deposits of thermal waters.
Keywords: climate change; Lesser Caucasus; Talysh zone; Caspian sea; hydrogeological massifs; mineral waters; mountain ranges; springs